Comparison of Salmonella enterica serovar Bovismorbificans 2011 hummus outbreak strains with non-outbreak strains. (April 2015) - Blaylock, Morris; Blackwell, Reginald; Merid, Sosina; Jackson, Scott; Kotewicz, Michael; Gopinath, Gopal; Ayers, Sherry L.; Abbott, Jason; Sabo, Jonathan; Ewing, Laura; Gangiredla, Jayanthi; Gebru, Solomon; et al.
Abstract: Eleven Salmonella enterica serovar Bovismorbificans isolates obtained from the U.S. District of Columbia during a 2011 hummus-associated foodborne outbreak were compared to 12 non-outbreak isolates. All isolates from the outbreak demonstrated a single PFGE pattern that was distinctly different from other isolates of S. Bovismorbificans as recorded in the PulseNet Database. Results from molecular analyses of the hummus-associated S. Bovismorbificans isolates indicate that the isolates from the outbreak were unique and have acquired an 80–90 kb plasmid. The impact of this study is that the information gained will add and expand our knowledge of diversity of the S. Bovismorbificans serovar. Highlights: Comparing Bovismorbificans outbreak versus non outbreak isolates. Identification of a plasmid in the outbreak isolates. Using multiple molecular approaches for characterization of plasmids.